2013
DOI: 10.4161/isl.24780
|View full text |Cite
|
Sign up to set email alerts
|

Small human islets comprised of moreβ-cells with higher insulin content than large islets

Abstract: For the past 30 y, data have suggested that unique islet populations exist, based on morphology and glucose sensitivity. Yet little has been done to determine the mechanism of these functional differences. The purpose of this study was to determine whether human islets were comprised functionally unique populations, and to elucidate a possible mechanism. Islets or pancreatic sections from 29 human donors were analyzed. Islets were isolated and measured for insulin secretion, cell composition and organization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 21 publications
4
43
1
Order By: Relevance
“…In this regard, Fujita et al (2011) reported that large islets secreted less insulin than small islets per islet equivalent. This is consistent with the fact that, in human pancreata, there is a higher proportion of beta cells in small islets (39 %) than in large islets (63 %), and its closer contact with blood vessels may affect insulin secretion (Farhat et al 2013). However, in a more recent study by Nam and colleagues (2010) the islets with the highest SI value had between 100 and 150 lm diameter in a heterogeneous population, which are in the size range of all methods.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this regard, Fujita et al (2011) reported that large islets secreted less insulin than small islets per islet equivalent. This is consistent with the fact that, in human pancreata, there is a higher proportion of beta cells in small islets (39 %) than in large islets (63 %), and its closer contact with blood vessels may affect insulin secretion (Farhat et al 2013). However, in a more recent study by Nam and colleagues (2010) the islets with the highest SI value had between 100 and 150 lm diameter in a heterogeneous population, which are in the size range of all methods.…”
Section: Discussionsupporting
confidence: 88%
“…Some articles have reported the superiority of rodent and human islets under 100-125 lm against large islets in in vitro and in vivo function (MacGregor et al 2006;Lehman et al 2007;Farhat et al 2013). In this regard, Fujita et al (2011) reported that large islets secreted less insulin than small islets per islet equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…In these 22 control experiments, total islet insulin content, measured at the end of the perifusions, averaged 6,500 Ϯ 660 ng/chamber (range 2,430 Ϫ13,580), which would correspond to 17.8 Ϯ 1.7 ng/islet (range 7.3-32.1), a value within the range of contents published by many laboratories (1,3,11,19,47).…”
Section: Basic Characteristics Of the Isletsmentioning
confidence: 66%
“…Although islet hand-picking may be required for valid metabolic or gene expression analyses, a nonselective procedure has the advantage of being more representative of the whole islet population in situ. Small islets, which are not spontaneously hand-picked, have been reported to secrete proportionally more insulin than large islets, with (19) or without (42) a greater stimulation index. Another study using 200 islets per perifusion chamber has also reported excellent consistency between the responses of 12 preparations (2).…”
Section: E645 Dynamics Of Insulin Secretion In Human Isletsmentioning
confidence: 99%
“…The capillaries surrounding islets have numerous fenestrations that facilitate nutrient exchange [ 11 ]. Heterogeneity in β-cell numbers between islets may be relevant to insulin secretion [ 12 ]. The activity of β-cells is synchronized both within and across islets.…”
Section: Islet Physiologymentioning
confidence: 99%